Investigating the effect of Aloe vera on the prevention and treatment of radiotherapy-induced oral mucositis in patients with head-and-neck cancer - Nadia Najafizade; Roya Mobini Dehkordi; Simin Hemati (Journal of Research in Medical Sciences, 2024)
Background: Oral mucositis is one of the main complications of radiotherapy (RT) while treating head-and-neck cancers and can affect the patients’ treatment process and life. Therefore, this study evaluated the effect of Aloe vera on the prevention and treatment of radiotherapy-induced oral mucositis (RIOM) in patients with head-and-neck cancer. Materials and Methods: This was a double-blind clinical trial performed in 2019 on 75 patients with head-and-neck cancer. Patients were randomly assigned to two groups receiving gargles of 5 cc Aloe vera and the same dose of placebo mouthwash three times a day, respectively. Then, the incidence and severity of RIOM were evaluated and compared between the two groups over 6 weeks of RT. Results: There was no significant difference between the two groups in terms of the severity of RIOM from the 1st to 3rd weeks of RT (P > 0.05). However, the severity of RIOM in the 4th, 5th, and 6th weeks of RT was significantly lower in the Aloe vera group compared with the placebo group (P < 0.05). Conclusion: According to the results of the present study, the long-term use of Aloe vera mouthwash can reduce the severity of RIOM.